2019
DOI: 10.1101/716266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neural bases of resilient cognitive systems: Evidence of variable neuro-displacement in the semantic system

Abstract: The purpose of this study was to initiate exploration of an equally-important research goal: what are the neurocomputational mechanisms that make these cognitive systems "well engineered" and thus resilient across a range of performance demands and to mild levels of perturbation or even damage? We achieved this aim by investigating the neural dynamics of the semantic network with two task difficulty manipulations. We found that intrinsic resilience-related mechanisms were observed in both the domain-specific s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Similarly, the enhanced semantic performance after 20 Hz rTMS over the left ATL might be attributed to not only the increased cortical excitability at the target site but also the enhanced connectivity within the semantic network. Our recent investigation examining the semantic network showed that there were up-regulated regional activation in the bilateral ATL, left IFG and posterior middle temporal gyrus (pMTG) and the increased functional connectivity between the semantic regions (e.g., the ATL-connectivity, ATL-IFG connectivity, and IFG-pMTG connectivity) in the challenging semantic decision making ( Jung and Lambon Ralph, 2019 ). The enhanced connectivity within the semantic network contributed to better semantic performance with increased task demands.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the enhanced semantic performance after 20 Hz rTMS over the left ATL might be attributed to not only the increased cortical excitability at the target site but also the enhanced connectivity within the semantic network. Our recent investigation examining the semantic network showed that there were up-regulated regional activation in the bilateral ATL, left IFG and posterior middle temporal gyrus (pMTG) and the increased functional connectivity between the semantic regions (e.g., the ATL-connectivity, ATL-IFG connectivity, and IFG-pMTG connectivity) in the challenging semantic decision making ( Jung and Lambon Ralph, 2019 ). The enhanced connectivity within the semantic network contributed to better semantic performance with increased task demands.…”
Section: Discussionmentioning
confidence: 99%
“…The ATL is a trans-modal hub in semantic memory [ 83 ]. Recent work has demonstrated significant coupling between the ATL and mPFC when the semantic demand was increased in a given task [ 84 ]. These findings suggest the involvement of semantic processing when the morpheme boundary is positioned between syllables.…”
Section: Discussionmentioning
confidence: 99%